The City of São Paulo's Environmental Quota: A Policy to Embrace Urban Environmental Services and Green Infrastructure Inequalities in the Global South - Caetano, Paulo Mantey Domingues; Pereira, Hélia Maria Santa Bárbara; Figueiredo, Lara Cavalcanti Ribeiro; Sepe, Patrícia Marra; Giatti, Leandro Luiz (Frontiers in Sustainable Cities, 2021)
In 2013 the urban authority for São Paulo city, Brazil, was interested in incorporating environmental aspects into the urban licensing process of diverse urban developments. To overcome concepts related simply to soil sealing, the initiative gave rise to a wide range of principles associated with environmental services and the consideration that green areas in this megacity are unequally distributed. Given the costs involved in analyzing each case and the legal uncertainty among entrepreneurs, it has become a tradition in Brazil for authorities in charge of urban licensing to follow general regulations rather than case-by-case studies, except in high-impact developments. In response, the São Paulo municipal government developed during the period from 2013 to 2016 a governing instrument to deal with these issues, known as the Environmental Quota (EQ). For that, the following guiding principles were established: (a) it should have a solid theoretical basis, with incentives for consistent public participation; (b) it should be flexible in such a way that it can provide a general framework within which a project designer can make decisions, rather than a set of rigidly determined solutions; and (c) it should consider inequalities in the availability of urban green infrastructure throughout the city. This paper will first detail the political-institutional context in which the EQ and its guidelines were established and implemented, then provide a general overview of the tool and the theoretical frameworks within which it was developed, and, finally, discuss the complex social decision-making process of its legal constraints. Moreover, it analyzes the implementation and application of the EQ to examine its effectiveness and how it relates to the city's gentrification. Furthermore, it is considered the replicability potential of the EQ to expand both the supply and distribution of green infrastructure and environmental services throughout the urban environment and, thus, contribute toward mitigating the intricate problems of urban environments in the Global South.